2024
DOI: 10.1002/acp.4194
|View full text |Cite
|
Sign up to set email alerts
|

Reasoning versus prior beliefs: The case of COVID‐19 fake news

Vladimíra Čavojová,
Matej Lorko,
Jakub Šrol

Abstract: We conduct a survey on a large representative sample of Slovak population to examine the role of analytic thinking, scientific reasoning, conspiracy mentality, and conspiracy beliefs in trust in COVID‐19 fake news and willingness to share it. We find that the ability to distinguish between fake and real news about COVID‐19 is significantly negatively correlated with conspiracy mentality and with beliefs in pandemic‐related conspiracy theories. Analytic thinking is not a significant predictor. Although fake new… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 75 publications
(114 reference statements)
0
0
0
Order By: Relevance
“…For example, Čavojová et al (2024) found that when disinformation about COVID-19 was consistent with preexisting opinions, people were more willing to share it compared with belief-consistent real news. Higher belief in disinformation and lower ability to distinguish between real news and disinformation has been also linked to conspiracy mentality (Čavojová et al, 2024;Szebeni et al, 2021). Moreover, if facts contradict core beliefs and pose threat to one's social identity, people are often motivated to protect their beliefs by rejecting these facts (Ditto et al, 2019;Friesen et al, 2015;Liu & Ditto, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…For example, Čavojová et al (2024) found that when disinformation about COVID-19 was consistent with preexisting opinions, people were more willing to share it compared with belief-consistent real news. Higher belief in disinformation and lower ability to distinguish between real news and disinformation has been also linked to conspiracy mentality (Čavojová et al, 2024;Szebeni et al, 2021). Moreover, if facts contradict core beliefs and pose threat to one's social identity, people are often motivated to protect their beliefs by rejecting these facts (Ditto et al, 2019;Friesen et al, 2015;Liu & Ditto, 2013).…”
Section: Discussionmentioning
confidence: 99%